FUNGSI SOSIAL PERPUSTAKAAN DAN GERAKAN LITERASI DALAM MEMBANGUN BUDAYA MEMBACA DI KALANGAN SISWA MADRASAH - Laili Rohmadhoni Novita Fitri, Noer; Nisak, Choirun; Dasuki, Marum; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
This study explores the role of libraries and literacy movements in fostering a reading culture among students at Madrasah (Islamic schools). Libraries, as central hubs for literacy, provide essential resources that contribute to the development of students' knowledge and critical thinking. The study uses qualitative methods to examine the implementation of literacy programs in Madrasah and their impact on reading habits. The findings indicate that libraries and literacy movements not only enhance students' academic performance but also support the spiritual and moral development of students. The study concludes by suggesting strategies for improving literacy programs in Islamic schools and their role in fostering a reading culture in line with Islamic values.